SUCCESSFUL IMAGE OF THE LITERARY CRITICISM IN THE SECOND DECADE OF THE TWENTIETH CENTURY - Gilk, Erik (Bohemica Olomucensia, 2014)
TICHY, Martin et al. (2013). Desata leta v podobach kritiky. V Opave: Slezska univerzita.